2018
DOI: 10.1111/jce.13638
|View full text |Cite
|
Sign up to set email alerts
|

Common and distinctive electrocardiographic characteristics and effective catheter ablation of idiopathic ventricular arrhythmias originating from different areas of ventricular septum adjacent to atrioventricular annulus

Abstract: Distinctive ECG characteristics of PVCs/IVTs originating from VS-AVA aid in origin localization guiding effective RFCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A number of studies (Chen et al, 2018; Wu et al, 2013; Xu et al, 2018; Zhang et al, 2018, 2019) have shown that PVCs originating from the tricuspid annulus reflected extensive ECG characteristics; most I, aVL, V 5 , and V 6 leads reflected unidirectional R‐waves, and the amplitude of the R‐wave in lead I was larger than the R‐wave in the sinus rhythm. However, the anterior lead may indicate different characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies (Chen et al, 2018; Wu et al, 2013; Xu et al, 2018; Zhang et al, 2018, 2019) have shown that PVCs originating from the tricuspid annulus reflected extensive ECG characteristics; most I, aVL, V 5 , and V 6 leads reflected unidirectional R‐waves, and the amplitude of the R‐wave in lead I was larger than the R‐wave in the sinus rhythm. However, the anterior lead may indicate different characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (Chen et al, 2018;Wu et al, 2013;Xu et al, 2018;Zhang et al, 2018Zhang et al, , 2019 Lu (Lu et al, 2016) reported that the ECG features of the tricuspid annulus and PVCs originating in the RVOT junction were as follows:…”
Section: Ta B L E 1 Baseline Patient Datamentioning
confidence: 99%
“…Briefly, it could be described as three steps. Step 1: Pre-judgement of left or right PHVAs according to the QRS morphology in lead V1 and precordial transitional zone ( 13 ). The “R”/“qR(s)” pattern in V1 and precordial transitional zone ≤ V1 indicated a left PHVA.…”
Section: Methodsmentioning
confidence: 99%
“…Most VAs have an aortic root, left ventricular (LV) septum, or right ventricular outflow tract origin [ 1 , 4 , 5 ]. However, about 5% to 10% of VAs have a rare origin adjacent to the mitral annulus (MA) [ 6 , 7 ]. MA-VAs can be divided into epicardial MA-VAs and endocardial MA-VAs, which are very different in the ablation treatment [ 5 ].…”
Section: Introductionmentioning
confidence: 99%